Propagation of Jackfruit by Modified Cleft Grafting as Influenced by Time of Operation (Progressive Agriculture, 2013)
The experiment was conducted to study the effect of time (season) of grafting on the performance of modified cleft grafting of Jackfruit at the BAU Germplasm Centre (GPC) of Fruit Tree Improvement Project (FTIP) of the Department of Horticulture, Bangladesh Agricultural University, Mymensingh. The experiment consisting ten levels of grafting times, viz., 30th March, 15th April, 30th April, 15th May, 30th May, 15th June, 30th June, 15th July, 30th July, 15th August, was laid out in RCBD with three replications. The results revealed that grafting done on 14th August showed the highest success (39%) and took the lowest time to first flush and first leaf opening (4.66 and 5.00 days, respectively) whereas the success rates were very low at the months of March, April and May. Likewise the highest vegetative growth of the grafted plants in terms of height, diameter, number of leaves, length and breadth of the leaves was found with grafting done on 14th August.DOI: http://dx.doi.org/10.3329/pa.v19i2.16930 Progress. Agric. 19(2): 67 - 74, 2008